2009
DOI: 10.1002/ajpa.21217
|View full text |Cite
|
Sign up to set email alerts
|

Enthesopathies as occupational stress markers: Evidence from the upper limb

Abstract: Enthesopathies--that is, "musculo-skeletal stress markers"--are frequently used to reconstruct past lifestyles and activity patterns. Relatively little attention has been paid in physical anthropology to methodological gaps implicit in this approach: almost all methods previously employed neglect current medical insights into enthesopathies and the distinction between healthy and pathological aspects has been arbitrary. This study presents a new visual method of studying fibrocartilaginous enthesopathies of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
341
1
25

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 233 publications
(385 citation statements)
references
References 49 publications
14
341
1
25
Order By: Relevance
“…Mariotti et al [14] and Villotte et al [21] stated that osteophytic enthesopathies are generally more pronounced in elderly individuals, a finding which reflected unilaterally in both cases of this report. As a result, Villotte et al [21] reported that the incidence of enthesopathies were higher on the right side than on the left side. Although the frequency of enthesopathies is deemed to be greater in males, this report was notably focused on females [14].…”
Section: Discussionsupporting
confidence: 65%
See 2 more Smart Citations
“…Mariotti et al [14] and Villotte et al [21] stated that osteophytic enthesopathies are generally more pronounced in elderly individuals, a finding which reflected unilaterally in both cases of this report. As a result, Villotte et al [21] reported that the incidence of enthesopathies were higher on the right side than on the left side. Although the frequency of enthesopathies is deemed to be greater in males, this report was notably focused on females [14].…”
Section: Discussionsupporting
confidence: 65%
“…The "activity-specific" nature of the upper limb osteology is the focal point in bioarchaeology for the geo-social exploration of ancient human civilizations [11,14,21]. Recent studies have redefined the enthesis as an organ comprising of interconnected anatomical tissue performing the common function of stress dissipation [15,20].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These entheseal changes include surface irregularity, hyperostotic reactions (i.e. enthesophytes), osteolytic reactions (erosions) and neo vascularization (Mariotti et al, 2004(Mariotti et al, , 2007Cardoso and Henderson, 2010;Villotte et al, 2010).…”
Section: Brief State Of the Artmentioning
confidence: 99%
“…Descriptions of other attempts to reconstruct past behaviours from bone analysis can be found in Jurmain (1999) and in Pearson and Buikstra (2006). After the Workshop, several papers that discussed the occurrence of entheseal changes in known occupation samples (Alves- Cardoso and Henderson, 2010;Niinimäki, in press;Villotte et al, 2010) and archaeological samples (Molnar, 2010;Molnar et al, in press) have been published.…”
Section: Brief State Of the Artmentioning
confidence: 99%